Heart failure in patients with rheumatoid arthritis is clinically different and has a worse prognosis. Issue 5 (October 2008) - Cardiel, Mario H
Evaluation of: Davis JM III, Roger VL, Crowson CS, Maradit Kremers H, Therneau TM, Gabriel SE: The presentation and outcome of heart failure in patients with rheumatoid arthritis differs from that in the general population. Arthritis Rheum. 58, 2603––2611 (2008). A community-based cohort study was undertaken in Olmsted County, Minnesota, USA, from 1979 to 2000 to compare the clinical presentation, management and outcome of incident heart failure in patients with rheumatoid arthritis (RA) compared with non-RA patients. This paper by Davis et al. studied 103 patients with RA and 852 non-RA patients who were compared with age- and sex-adjusted rates and multivariable logistic regresion models to evaluate clinical features and mortality. Patients with RA were more often female and had less frequency of obesity, hypertension and ischemic heart disease. Patients with RA had fewer typical symptoms of heart failure and were less likely to have undergone echocardiography. Patients with RA were more likely to have preserved ejection fraction. Mortality at 1 year was higher in RA patients (35 vs 19%; multivariable hazard ratio: 1.89; 95% confidence interval: 1.26––2.84). These findings support a more subtle clinical presentation, but increased mortality from heart failure in RA patients.